Sensor duplo para perfilamento de velocidade em misturas bifásicas - Botton, Luís Felipe Silveira (2019)
The importance of multiphase flow measurement in many industries today is widely known. In the oil industry in particular, this type of flow is found within wells, flow lines and risers from the oil reservoir to the platform. Two-phase liquid-gas flow, a special type of multiphase flow formed by only liquid and gas phase, is of particular importance because of its recurrence and the effects produced in various processes and stages in oil exploration. Therefore, knowledge of flow parameters is fundamental for the design and sizing of production units and equipment, definition of constraints and efficiency parameters, process-related costs, safety factors for personnel and equipment. Traditional multiphase flow measurement techniques in the industrial environment are mainly based on the separation of multiphase flows into their different phases. Phase separation requires bulky, slow and expensive separators. This method has not satisfactorily met the increasing demands on oil production levels associated with stricter quality specifications and new exploration boundaries reached. Consequently, the development of a flow sensor for online and inline measurements is required to provide flow status information. To achieve this goal, a twin capacitive flow sensor called DIS was used in conjunction with a phase fraction sensitivity matrix and a spatial velocity sensitivity matrix. This study developed the spatial velocity sensitivity matrix by applying the inverse problem approach to the phase fraction sensitivity map of each DIS layer. In this strategy, the individual sensitivity of each upstream and downstream receiver was combined by the back-projection technique producing the spatial velocity sensitivity matrix. Then, the proposed technique was tested by processing synthetic data and experimental flow data with image reconstruction algorithms using the velocity sensitivity and original phase fraction matrices. This procedure allowed obtaining sufficient data to evaluate the velocity profile, the cross section of the gas phase distribution and, consequently, to estimate the gas phase volumetric flow rate by applying simple fluid mechanics equation. The results show that the new technique presented is viable, well adaptable and has great potential. Although it has explicit flow pattern dependence, for some flow conditions the method can achieve results with a deviation of less than 5% and, on average, gas flow is within 20% uncertainty.